What can we learn from indigenous peoples law and methodology? - De Gregorio, Valentina; Parola, Giulia; Porrone, Arianna; Poto, Margherita Paola; Tsiouvalas, Apostolos (Unicuritiba, 2021)
Source at http://revista.unicuritiba.edu.br/index.php/RevJur/article/view/5171 . Objective: The paper analyses the deep contributions of Indigenous knowledge on enriching and encouraging change to laws and research and training the Western legal systems to listen to other voices that have been silenced for centuries. Methodology: The argumentation developed in the paper is based on interdisciplinary research (intertwining social and legal reflections on the three principles of inclusion, coexistence, and resilience) and on a novel approach to comparative law, which includes elements of indigenous law and empirical research (e.g. in the part of the Sea Sámi and traditional fishers), and therefore goes beyond the desk-based comparison of Western-based state laws (e.g. in the last section). Results: The paper is divided into four sections: section 1 examines the constituent elements drawn from the training on Indigenous law and methodology: inclusion, coexistence, and resilience. Section 2 refers to the need of inclusion and interaction between different legal orders (state law and Indigenous and traditional peoples’ legal orders), focusing on the case study of the Belo Monte Hydroelectric Power Plant in the Xingu Basin, Brazil. Section 3 develops the theme of coexistence analysing the Indigenous legal traditions of the Northern Coastal peoples in the county of Troms (Sea Sámi and traditional fishers), still kept alive and somehow co-existing with the Norwegian system of coastal governance. Section 4 focuses on resilience with a case study on the Arctic and the local and Indigenous peoples’ response to the challenges posed by climate change. Finally, the concluding remarks open the floor for a reflection on a new ontology of the relationship between humans and the natural world. Contributions: The study addresses a topic still unfamiliar to the academic world, by adopting a novel approach to comparative law that bridges indigenous and non indigenous views, and by proposing a new understanding of inclusion, ...